2007
DOI: 10.1007/s00466-007-0210-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on finite element methods for dynamic fracture

Abstract: The performance of finite element methods for dynamic crack propagation in brittle materials is studied. Three methods are considered: the extended finite element method (XFEM), element deletion method and interelement crack method. The extended finite element method is a method for arbitrary crack propagation without remeshing. In element deletion methods, elements that meet a fracture criterion are deleted. In interelement crack methods, the crack is limited to element edges; the separation of these edges is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
230
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 383 publications
(242 citation statements)
references
References 36 publications
6
230
1
5
Order By: Relevance
“…A pre-notched rectangular panel is subjected to a uniform traction applied as a step function on the two edges parallel to the notch. This experiment has been simulated computationally by other authors [42,43], and related experimental results were reported by different researchers [44,45]. Ramulu and Kobayashi [44] observed experimentally that a major crack starts to propagate from the notch tip to the right, which branches into two cracks at a certain point during the experiment, see Figure 22 for the sketch of the experimental result.…”
Section: Dynamic Crack Branchingmentioning
confidence: 64%
See 1 more Smart Citation
“…A pre-notched rectangular panel is subjected to a uniform traction applied as a step function on the two edges parallel to the notch. This experiment has been simulated computationally by other authors [42,43], and related experimental results were reported by different researchers [44,45]. Ramulu and Kobayashi [44] observed experimentally that a major crack starts to propagate from the notch tip to the right, which branches into two cracks at a certain point during the experiment, see Figure 22 for the sketch of the experimental result.…”
Section: Dynamic Crack Branchingmentioning
confidence: 64%
“…A pre-notched rectangular panel is subjected to a uniform traction applied as a step function on the two edges parallel to the notch. This experiment has been simulated computationally by other authors [42,43], and related experimental results were reported by di↵erent shear strains develop leading to high principal tensile strains and crack initiation at the left side of the notch tip.…”
Section: Dynamic Crack Branchingmentioning
confidence: 86%
“…This therefore makes eXtended Finite Element Method (XFEM) a more sensible choice than other approaches by bypassing the need re-mesh. To examine the applicability of the quasi-explicit CZM approach proposed here for dynamic macro-crack propagation it is compared to the following previously discussed approaches [22,23] The main difference of the approach used in this work compared to previous CZM approaches is that XFEM enrichment is used to insert a crack along a pre-defined path with a phenomenological cohesive law, meaning that the crack definition is no longer purely along element boundaries. It is anticipated that the new approach will provide further insight into the nature of modelling dynamic fracture.…”
Section: Crack Propagation Algorithmmentioning
confidence: 99%
“…The size of the geometry was considered such that the dissipated energy from the fast fracture event did not have enough time to reflect back to interact with the propagating crack before it arrested meaning the crack was purely driven by the rate-dependent fracture energy. When modelling this experiment using the quasiexplicit CZM approach, the initial material properties were chosen to be the ones used previously such that: E = 3.24 GPa, Mass Density ρ = 1190 kg/m 3 , with the Rayleigh Wave speed considered to be c r = 930 ms -1 [15,23]. The initial parameters for the cohesive law were also selected to be those used previously by Song et al and The contor stress plots for the initial notch and final crack are shown in Fig.…”
Section: Application 1 -Pmmamentioning
confidence: 99%
“…However, they show some limitations mainly related with the objectivity, computational cost and the overall ability to predict experimental tests [36]. Different alternatives have been adopted to model crack nucleation and propagation in a dynamic setting.…”
Section: Introductionmentioning
confidence: 99%